INTERGENERATIONAL TRANSMISSION OF GAYO LANGUAGE IN BENER MERIAH, ACEH - Ratri Candrasari; Harinawati Harinawati; Subhani Subhani; Safriandi Safriandi; Ichsan Ichsan (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2023)
This study aims to (1) describe the level of existence of the Gayo language and (2) formulate recommendations for strengthening intergenerational transmission of the Gayo language spoken by the tribes in Aceh. This research is studied using a Linguistic-Anthropological perspective, namely a review that analyzes the relationship between culture and language. The research approach used is mixed methods, quantitative and qualitative. To describe the level of existence of the Gayo language, data on language use and language attitudes are needed by distributing questionnaires. Furthermore, the data were analyzed based on the generation group and the realm of language use. The measurement results were then discussed through FGDs involving Gayo ethnic community leaders, Gayo youth, Reje village, Head of the Education and Culture Office. The results of the study show that the Gayo language is still strong in the realm of kinship, social and custom. Gayo language is also still used in almost all generation groups except for the 4th generation, namely those aged <50 years who are at a strong level but are in danger of experiencing a shift. In the realm of association, poetry is still alive, both in important ceremonies and in association, especially advice poetry. Customary law in Gayo land is still upheld so that the Gayo language is still very much alive because qanuns or customary regulations are written in Gayo language. In addition, the effort to transmit language to the younger generation is the Pemangu ceremony, which is the ceremony of handing over children from parents represented by the Gayo Traditional Council to teachers at school.Penelitian ini bertujuan untuk (1) mendeskripsikan tingkat eksistensi bahasa Gayo dan (2) merumuskan rekomendasi penguatan transmisi antargenerasi bahasa Gayo yang dituturkan oleh suku-suku di Aceh . Penelitian ini dikaji dengan menggunakan perspektif Linguistik-Antropologi, yaitu tinjauan yang menganalisis hubungan antara budaya dan bahasa. Pendekatan penelitian yang digunakan adalah metode campuran, kuantitatif, dan kualitatif. Untuk menggambarkan tingkat keberadaan bahasa Gayo diperlukan data penggunaan bahasa, dan sikap berbahasa dengan cara menyebarkan kuesioner. Selanjutnya data dianalisis berdasarkan kelompok generasi dan ranah penggunaan bahasa. Hasil pengukuran tersebut kemudian dibahas melalui FGD yang melibatkan tokoh masyarakat etnis Gayo, pemuda Gayo, kampung Reje, Kepala Dinas Pendidikan dan Kebudayaan. Hasil penelitian menunjukkan bahwa bahasa Gayo masih kuat dalam ranah kekeluargaan, sosial, dan adat. Bahasa Gayo juga masih digunakan hampir di semua kelompok generasi kecuali generasi ke-4, yaitu mereka yang berusia <50 tahun yang berada pada level kuat namun terancam mengalami pergeseran. Dalam ranah pergaulan, puisi masih tetap hidup, baik dalam upacara-upacara penting maupun dalam pergaulan, khususnya puisi nasehat. Hukum adat di tanah Gayo masih ditegakkan sehingga bahasa Gayo masih sangat hidup karena qanun atau peraturan adat tertulis menggunakan bahasa Gayo. Selain itu upaya transmisi bahasa kepada generasi muda yaitu dengan upacara Pemangu yaitu upacara penyerahan anak dari orang tua yang diwakili Dewan Adat Gayo kepada guru di sekolah.